Selection the method of natural gas preparation for transportation through main gas pipelines - O. Yu. Manikhin; V. V. Shalay; E. V. Khodоreva (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
When designing natural gas drying equipment, the possibility of implementing an integrated approach to determine the rational technical and economic indicators of the technological devices under consideration is of great importance. This makes it possible to achieve maximum energy efficiency from the operated equipment for each specific field. One of the important tasks to be solved in the development of gas fields is the choice of a method and appropriate technological equipment according to a variety of criteria, including operating costs and the cost of devices, plant performance, metal consumption, replicability of the technology in question, etc. One of the ways to solve such a problem is the application of mathematical methods of system analysis in complex decision-making problems, in particular, the method of analyzing hierarchies.